Utilization of Janus-silica/surfactant nanofluid without ultra-low interfacial tension for improving oil recovery. (31st December 2020) - Liu, Peisong; Yu, Huanhuan; Niu, Liyong; Ni, Dongdong; Zhao, Qianyu; Li, Xiaohong; Zhang, Zhijun
Graphical abstract: Highlights: Janus-SiO2 nanofluid is prepared by a novel chemical etching method. Pure Janus-SiO2 nanofluid presents a IFT of about 0.09 mN/m with kerosene. Interfacial behaviours of three surfactants are improved by Janus-SiO2 . The Janus-SiO2 /surfactant nanofluid shows promising potential for enhanced oil recovery. Janus-SiO2 nanofluid has been industrialized due to its low-cost and simple preparation procedure. Abstract: Janus nanoparticles with amphiphilic surfaces could be of particular significance for enhanced oil recovery (EOR) of reservoirs. However, currently available methods for preparing Janus nanoparticles are often complicated. Here we present a highly efficient and easily scalable one-step chemical etching method with NaOH as the etching agent for fabricating amphiphilic Janus-SiO2 nanoparticles. The structure, interfacial behavior and improved oil recovery (IOR) potential of the as-prepared Janus-SiO2 nanoparticles were systematically studied. Results show that Janus-SiO2 nanoparticles with size less than 10 nm exhibit good dispersibility in water and amphiphilicity as well. When combined with various surfactants, they can significantly improve the oil recovery upon simulated water flooding, due to their good abilities to increase the sweep efficiency of surfactants and reduce the interfacial tension of oil–water emulsion. Oil recoveries are improved by 7.4–9.8% with addition of Janus-SiO2 in surfactants compared to pure surfactant solutions, showing promising potential for EOR.